PENGEMBANGAN PROGRAM KOKURIKULER BERORIENTASI HOTS DALAM IMPLEMENTASI KURIKULUM MERDEKA - Yoga Adi Pratama, - (2023)
Various attempts were made to increase HOTS, however, these efforts were only at the intracurricular level. Success in intracurricular research is felt to be less comprehensive. Answering the problems above, co-curricular exist as an alternative effort to increase HOTS. Co-curricular is an intra-curricular support program that is carried out outside of class hours. In the context of the independent curriculum, the co-curricular is carried out in the form of the Pancasila Student Profile Strengthening Project (P5), so the purpose of this study is to develop HOTS-oriented co-curricular in the implementation of the independent curriculum. The method used is Design-Based Research (DBR). The participants in this research were students of class V (Phase C). The research instruments used were needs assessment questionnaires, interview guidelines, and observation sheets. The first finding in the needs assessment shows that aspects of co-curricular goals and content are sustainable lifestyles. The aspect of the process is the investigation of the creation of works/ideas, and exhibitions. The aspects of the assessment are written tests and work creation. The second finding is the development of learning outcomes on a sustainable lifestyle by infusing HOTS. The third finding is designing a HOTS-oriented backward design which is then developed into a P5 module. The fourth finding is the result of a limited trial which concludes that HOTS-oriented co-curricular positively impact students' HOTS. This is evidenced by the t-test which concludes that there is a significant difference between the pretest and posttest. The average posttest is in the good category while the pretest is in the poor category. The formative assessment results through rubric P5 are all in the developing category as expected (good). The results of this study provide a signal that in the development of HOTS it is not only an intra-curricular domain, but also co-curricular. The conclusion of this study is that HOTS-oriented co-curricular development has a positive impact on increasing student HOTS.